Non-adherence to diet and exercise recommendations amongst patients with type 2 diabetes mellitus attending Extension II Clinic in Botswana - Adewale B. Ganiyu; Langalibalele H. Mabuza; Nomsa H. Malete; Indiran Govender; Gboyega A. Ogunbanjo (AOSIS, 2013)
Background: Patients diagnosed with type 2 diabetes mellitus in Extension II Clinic in Botswana have difficulty in adhering to the lifestyle modifications recommended by healthcare practitioners. Poor adherence to lifestyle recommendations leads to poor control of the condition and consequently to complications. Objectives: The aim of the study was to determine reasons for poor adherence to lifestyle recommendations amongst the patients. The objectives were to determine: reasons for pooradherence to dietary requirements, exercise recommendations, the support they had in adhering to the recommendations, and their understanding of the role of dietary and exercise requirements in the management of their condition. Method: This was a cross-sectional descriptive study. The sample comprised of 105 participants. Data on participants' baseline characteristics and adherence to dietary and exercise habits were analysed using the SPSS 14.0 version. Results: The sample of 104 participants comprised of 61 (58.7%) women. The rates of nonadherence to diet and exercise were 37% and 52% respectively. The main reasons for nonadherence to diet were: poor self-discipline (63.4%); lack of information (33.3%) and thetendency to eat out (31.7%). The main reasons for non-adherence to exercise were: lack of information (65.7%); the perception that exercise exacerbated their illness (57.6%) and lack of an exercise partner (24.0%). Conclusion: There was a relatively high rate of non-adherence to both diet and exercise recommendations by patients suffering from type 2 diabetes mellitus at Extension II Clinic,Botswana, with non-adherence to exercise recommendations more common.